Effect of gamma-oryzanol, oryzanol rich fraction and fractioned components on colorectal cancer cell line (HT-29) and cytokine production by human peripheral blood mononuclear cells - Alishavandi, Sima (2011)
A number of reports reveal that cells use antioxidants as part of the signaling process, responsible for activating an important mechanism for eliminating cancer cells, via programmed cell death (apoptosis). Some study also focused on the capability of antioxidants to inhibit cancer cell growth through modulation of immune system. The present study was to evaluated the Cytotoxicity effect of gamma-oryzanol (OR), oryzanol rich fraction (ORF) and major components of OR, i.e. cycloartenyl ferulate, 24-methylene cycloartanyl ferulate, Campesteryl ferulate and sitosteryl ferulate, on colorectal cancer cell line (HT-29), and immunomudulatory effects of those components on human peripheral blood mononuclear cell (PBMC). Cytoxicity study was performed on HT-29 by using MTS assay .The result showed that OR , ORF, cycloartenyl ferulate and 24- methylene cycloartanyl ferulate significantly inhibited cell growth with the IC50 value of 98, 80, 75 and 22μg/ml after 72h respectively. The results of AO/PI staining showed that after treated cells in IC50 value of OR, ORF, cycloartenyl ferulate and 24-methylene cycloartanyl ferulate for 72h percentages of apoptotic cell increased to 18, 38, 19 and 43 % compared to untreated group (1.63%) and the results of cell cycle assay showed an arrest in all treated group by increase in G2/M phase and a decrease in G0/G1 phase respectively. The results of AO/PI and cell cycle was confirmed by Annexin V-FITC/PI and data showed that OR, ORF, cycloartenyl ferulate and 24-methylene cycloartanyl ferulate after 72h in IC50 value induced 21, 30, 18 and 40% apoptosis in HT-29 cell respectively as compared to untreated group (2%). The results demonstrated that caspase -3 activities of HT-29 cells after treated with IC50 value of those components in 72h increased up to 0.64, 0.73, 0.51 and 0.76 % compared to untreated group (0.17%) respectively. And caspase -9 activity also increased up to 2.17, 3.75, 2.23 and 6.21 % as compared to untreated group (0.06%).Immunomodulatory study revealed that OR, ORF, cycloartenyl ferulate and 24-methylene cycloartanyl ferulate were able to stimulated the proliferation of PBMC even at low concentration (1 μg/ml) and did not inhibit on at higher concentration (400 μg/ml) in all treated group. The results also demonstrated that those component stimulated interferon-gamma (IFN-γ) and interleukin-2 (IL-2), production in PBMC after 72h. Data revealed that OR, ORF, cycloartenyl ferulate and 24-methylene cycloartanyl ferulate stimulated production of IL-2 up to 51, 155, 120 and 162 pg/ml respectively as compared to untreated group (2.23 pg/ml) and the production of IFN-γ also increased up to 32, 43, 45 and 47 pg/ml as compared to untreated group ( 6.6 pg/ml). Based on the result presented, the components OR, ORF, cycloartenyl ferulate and 24-methylene cycloartanyl ferulate can act as sytotoxic and immunomodulatory agent which are very useful in treating cancer and enhancing the immune system.